Applying the AWIN Protocol for Animal Welfare Assessment for Sheep in Kef and Siliana, Tunisia - Tebourbi, Ons; Atallah, Elie; Abbassi, Takwa; Ben Salem, Imene; Dalla Costa, Emanuela; Rekik, Mourad (International Center for Agricultural Research in the Dry Areas, 2024)
Under CGIAR’s Agroecology initiative, this work constitutes a first attempt to evaluate the sheep welfare status in the Tunisian Agroecological Living Landscape (ALL), El Kef and Siliana, with the aim of providing farmers with low cost and low-input targeted solutions to improve their sheep flocks’ management practices at first place and initiating the elaboration of an animal welfare guideline for sheep farming in Tunisia at second place. This document provides a description of the different activities conducted to assess sheep welfare conditions in Tunisian ALL, a summary of their main results, and suggests several propositions for improving sheep welfare in Tunisia.